MODERN ASPECT TO PROBLEM OF CRITICAL LIMB ISCHEMIA CAUSED BY MULTIFOCAL ATHEROSCLEROSIS (Spectrum Journal of Innovation, Reforms and Development, 2024)
Chronic obliterating diseases of the arteries of the lower extremities (CVD) account for more than 20% of all CVD types, which corresponds to 2–3% of the total population [9,17,25]. The incidence of diseases increases significantly in the elderly and senile: 0.3% of people aged 30 to 40 years, 1% of people aged 40 to 50 years, 2-3% of people aged 50 to 60 years, and 5-7% of people aged 70 and older [22,27]. According to authoritative publications and the results of modern large population-based studies (PANDORA, 2012; Russian Consensus Document, 2016), the prevalence of peripheral arterial disease varies from 5.8% in the United States and 7% in Russia, respectively, to 12.2% and 22.9% in France and Italy. In the United States [7,11], about 10% of people over 55 years of age have an asymptomatic form of CLD, and symptoms of intermittent claudication are noted in 5% of individuals.